A guide to national socialism : the Third Reich and Richard Wagner - McCalman, Godfrey Kevin (College of Music, 2024)
This study of Richard Wagner's life and works and their supposed influence on Adolf Hitler and the founders of the Third Reich was prompted by the readily available amount of extremely divergent opinion on the subject. Remarks such as the following are common: As long as Wagner's operas continue to be performed there remains the possibility of a return to some National-Socialist doctrine of salvation. 1 German intellectuals would not have opened their arms quite so readily to Hitler if they had not been prepared for it by Wagner, Bayreuth and the Wagnerians. 2 Wagner was He cared for monster who should prove a self-centred egotist of the worst kind. absolutely nobody. He was an anti-Semitic took other men's wives and money - he fascinating to play. 3 The music of the Nazis is not the Prelude to Die Meistersinger but the Horst-Wessel lied, they deserve nothing better and no other respect can be paid them. 4 The mere mention of Wagner's name in this connection often is enough to provoke considerable ho still ty, particular I y amongst Jews, and an almost inevitable reference to the Nazi regime.